Identity-Based Challenges in the Political Leadership of Sherly Tjoanda in North Maluku - Anatul Widiyanti; Nathania Aulia Damayanti; Ika Arinia Indriyani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the layered barriers faced by Sherly Tjoanda in constructing her political leadership identity in North Maluku as a leader simultaneously carrying three minority attributes: a woman, of Chinese descent, and a Christian in a predominantly Muslim region. Employing a qualitative case study approach, the research draws on public document analysis, media coverage, KPU electoral data, and recent academic literature (2022–2025). The theoretical framework integrates intersectionality (Crenshaw, 1989), the glass ceiling concept (Morrison et al., 1987), hegemonic masculinity (Connell, 1995), and transformational leadership theory (Burns, 1978; Bass, 1985). Findings identify three clusters of barriers: gender-structural barriers rooted in patriarchal norms and party recruitment systems, ethnic-religious identity barriers that mobilize majoritarian sentiment, and legitimacy barriers questioning her political agency. Nevertheless, Sherly successfully navigated these barriers through transformational leadership strategies characterized by empathy, a public service narrative, and the productive mobilization of public sympathy. Her victory with 51.68 percent of the vote in the 2024 regional election demonstrates that local democratic maturity can transcend identity boundaries. This study contributes to the intersectional framework in Indonesian women’s leadership scholarship and enriches the literature on transformational leadership within complex identity contexts in local politics.